Silver Nanoparticles Stabilized with Phosphorus-Containing Heterocyclic Surfactants: Synthesis, Physico-Chemical Properties, and Biological Activity Determination - Pisárčik, Martin; Lukáč, Miloš; Jampílek, Josef; Bilka, František; Bilková, Andrea; Pašková, Ľudmila; Devínsky, Ferdinand; Horáková, Renáta; Březina, Matěj; Opravil, Tomáš (Nanomaterials, 2021)
Phosphorus-containing heterocyclic cationic surfactants alkyldimethylphenylphospholium bromides with the alkyl chain length 14 to 18 carbon atoms were used for the stabilization of silver nanodispersions. Zeta potential of silver nanodispersions ranges from +35 to +70 mV, which indicates the formation of stable silver nanoparticles (AgNPs). Long-chain heptadecyl and octadecyl homologs of the surfactants series provided the most intensive stabilizing effect to AgNPs, resulting in high positive zeta potential values and smaller diameter of AgNPs in the range 50-60 nm. A comparison with non-heterocyclic alkyltrimethylphosphonium surfactants of the same alkyl chain length showed better stability and more positive zeta potential values for silver nanodispersions stabilized with heterocyclic phospholium surfactants. Investigations of biological activity of phospholium-capped AgNPs are represented by the studies of antimicrobial activity and cytotoxicity. While cytotoxicity results revealed an increased level of HepG2 cell growth inhibition as compared with the cytotoxicity level of silver-free surfactant solutions, no enhanced antimicrobial action of phospholium-capped AgNPs against microbial pathogens was observed. The comparison of cytotoxicity of AgNPs stabilized with various non-heterocyclic ammonium and phosphonium surfactants shows that AgNPs capped with heterocyclic alkyldimethylphenylphospholium and non-heterocyclic triphenyl-substituted phosphonium surfactants have the highest cytotoxicity among silver nanodispersions stabilized by the series of ammonium and phosphonium surfactants.